2020
DOI: 10.1177/1708538120952665
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular aortic repair with the Gore Excluder Conformable endograft in severe neck angulation: Preliminary experience and technical aspects

Abstract: Objectives Endovascular procedures are now the standard of care for endovascular aortic aneurysm repair but treatment of hostile proximal neck anatomy is still challenging. New endografts were brought to the market specifically designed to accommodate severe neck angulation. Authors describe a preliminary experience and early results using the Gore Excluder Conformable endograft (W. L. Gore & Associates, Flagstaff, Ariz) and its active control system in severe neck angulation with a standardized technical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…The first studies showed good results, without type IA endoleak, migration or secondary procedures. 19 However, long-term outcomes have to be evaluated.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The first studies showed good results, without type IA endoleak, migration or secondary procedures. 19 However, long-term outcomes have to be evaluated.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…12 To date, only few small clinical series on EVAR with this device have been reported in the literature, with lack of results on the severe angulated aortic neck. [12][13][14] The aim of this study was to report 2 years of singlecenter experience with CEXC Device in severe angulated neck AAAs.…”
Section: Introductionmentioning
confidence: 99%
“…In order to be labeled as hostile, the AAA neck has to have any of the following features: (1) >2 mm reverse taper within 1 cm below the renal arteries, (2) ≥60° angulation within 3 cm below renal arteries, (3) ≤10 mm neck length, (4) neck thrombus of ≥50% of circumference, and (5) >3 mm focal bulge in the neck ( 7 ). Others refer to the hostile aortic neck length as ≤15 mm ( 8 , 9 ), with this length being the minimum requirement for most endografts.…”
Section: Introductionmentioning
confidence: 99%